If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -6 = -12 + 8p Reorder the terms: -6 + 2p = -12 + 8p Solving -6 + 2p = -12 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. -6 + 2p + -8p = -12 + 8p + -8p Combine like terms: 2p + -8p = -6p -6 + -6p = -12 + 8p + -8p Combine like terms: 8p + -8p = 0 -6 + -6p = -12 + 0 -6 + -6p = -12 Add '6' to each side of the equation. -6 + 6 + -6p = -12 + 6 Combine like terms: -6 + 6 = 0 0 + -6p = -12 + 6 -6p = -12 + 6 Combine like terms: -12 + 6 = -6 -6p = -6 Divide each side by '-6'. p = 1 Simplifying p = 1
| 3-6v+6v=15+3v | | 30+4x=6x-35 | | 9x*-12x+4=0 | | -1(x-6)=8x-12 | | 8p-28=-22+9p | | 1000000+1=x | | 32x+8y=5600 | | 5(2m-5)=7-(m+3) | | -5a+6a=-10+3a | | 432=x(x-6)(x-6) | | -5p+8+6p=10 | | x+3x=4x | | .5x-1.5=-6.5 | | (180x-1800)/(x)(x-20) | | 3x-45-3x= | | x=5/8y | | Y^2+9=6y | | 38=0.4n | | 3n+2+1=-21 | | 7+(4+4)= | | 0.3x=26 | | x1/10 | | 11=x-5+8 | | 3n+2+1=-2 | | x(x-6)(x-2)=996 | | 49w=-8 | | 8(x-2)=2x+8 | | 15t-14=-14 | | 9=-5r-4r | | -1(x-6)= | | 8x^2+2x+9=0 | | -9(6n+4)=18-5n |